Analisa Perencanaan Bangunan Gedung Hijau Klas 1a Di Kota Jambi Menggunakan Pendekatan Partial Least Square (PLS) - Didik Yulianto; Hendi Matalata; Abdul Manap (Balitbangda Provinsi Jambi, 2023)
The climate challenge is essentially an energy challenge. With that in mind, policymakers around the world are trying to accelerate the adoption of clean energy technologies. Stronger policy support such as minimum performance standards is needed so that the building sector is on the right track towards a Zero Emission Scenario by 2050. PUPR Ministerial Regulation number 21 of 2021 concerning green building performance assessment which is a minimum performance standard as a government policy must be implemented in Indonesia. The districts/cities of Jambi province currently have not carried out green building construction at any time, both in terms of planning and implementation. Therefore, it is hoped that this policy can be implemented well from the aspect of building construction. This research aims to identify factors exploring the performance of green building criteria, environmental awareness and the implementation of workshops on the impact of barriers to green building construction. A qualitative approach was used in this research and data was collected from workshop participants in Jambi City. The analysis method was carried out using SmartPLS 3.0 qualitatively. From the results of the research conducted, environmental concern for barriers to green buildings has a significant influence, so it is important to socialize the impacts of global warming to the community, one of which is the role of implementing green buildings. The results of this research are expected to include workshops, training and outreach activities as well as policies in the form of PERDA providing incentives to the community so that they can trigger the interest of building owners Keywords: SmartPLS, Green Building.